Analysis of endophytic bacterial diversity of Puerariae thomsonii from different production areas and their correlation with secondary metabolites - Xu, Yang; Zeng, Lihua; Peng, Zheng; Chang, Nana; Wang, Ye; Zheng, Lingling; Ren, Yan; Li, Hui; Wang, Tielin (Frontiers in Microbiology, 2025)
IntroductionPuerariae thomsonii Benth is an important medicinal and edible plant, with its dried roots being widely used in traditional Chinese medicine. The secondary metabolites of P. thomsonii mainly contain flavonoid compounds that have beneficial effects on human health. Current researches on the secondary metabolites of P. thomsonii have primarily focused on the effects of external environmental factors, while studies investigating the impact of internal microorganisms on its secondary metabolites remain limited.MethodsIn this study, P. thomsonii roots were collected from five different regions in Jiangxi province to investigate the diversity of endophytic bacteria and their correlation with five isoflavones (puerarin, daidzin, genistin, daidzein, and genistein). The differences between endophytes and the content of five isoflavones were analyzed using high-throughput sequencing and UPLC methods. In addition, differences in endophytic bacteria across the samples from different productions were analyzed using LEfSe analysis. The functional capabilities of these bacteria were analyzed through PICRUSt2 to explore potential microbial functional traits.ResultsThe findings indicated that the alpha diversity of endophytic bacteria in P. thomsonii differed among production areas and the unique bacterial genera could be found in different areas. Four secondary metabolites in P. thomsonii were found to have a positive correlation with the diversity, evenness, and richness of endophytic bacterial communities using Spearman’s correlation analysis. Genera such as unclassified_f_ Xanthomonadaceae, Bosea, and Methylobacterium–Methylorubrum were significant positively correlated with one or more of these secondary metabolites.DiscussionThis research enriches the endophytic bacterial resources of P. thomsonii, provides a preliminary analysis of the correlation between plants and microorganisms, and offers a scientific basis for the future exploration and application of endophytic resources in P. thomsonii.